2005
DOI: 10.1007/s00244-003-0206-2
|View full text |Cite
|
Sign up to set email alerts
|

The Ratios of Individual Chemicals in a Mixture Determine the Degree of Joint Effect: The Climax Hypothesis

Abstract: Abstract.A new hypothesis, the Climax Hypothesis, is proposed to describe how the ratios of individual chemicals influence the joint effects of chemical mixtures. This hypothesis is derived from a generalized approach using ''isobolograms.'' With this hypothesis, one can predict that for a given mixture, a curvilinear correlation exists between the joint effects and the ratios of individual chemicals and that this curve has a climax at the equitoxic ratio. This prediction is supported by the observed toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…There were two pairs of inverted U-shaped relationships between the P i of components and the toxicities (pEC 30 , pEC 50 , pEC 80 ) of mixtures of EL and ED, and OD and OL. This phenomenon basically conformed to the climax hypothesis proposed by Lin et al [50]. The climax hypothesis concluded that there was a climax at the equitoxic ratio when plotting the toxic ratios of individual chemicals in mixtures versus their joint effects [51].…”
Section: Relationship Between Mixture Toxicity and Enantiomer Concentsupporting
confidence: 87%
See 1 more Smart Citation
“…There were two pairs of inverted U-shaped relationships between the P i of components and the toxicities (pEC 30 , pEC 50 , pEC 80 ) of mixtures of EL and ED, and OD and OL. This phenomenon basically conformed to the climax hypothesis proposed by Lin et al [50]. The climax hypothesis concluded that there was a climax at the equitoxic ratio when plotting the toxic ratios of individual chemicals in mixtures versus their joint effects [51].…”
Section: Relationship Between Mixture Toxicity and Enantiomer Concentsupporting
confidence: 87%
“…The variability of the blank control in the test was controlled within ±20%. The indicators of effect concentration EC 80 , EC 50 , and EC 30 are shown in Table 1. According to these indicators, the toxicity order of single enantiomers was OL ≥ OD > HL > HD > BD > BL > EL ≥ ED.…”
Section: Single Enantiomer Toxicitymentioning
confidence: 99%
“…5B) for the selected chemicals showed that different binary permutations produced synergistic joint effects except at very low values of k 1 which showed additive effects. Although the underlying reason for this ratio-dependent conversion is not known, it has been noted in previous mixture studies (e.g., see Lin et al, 2005; Tian et al, 2013a). …”
Section: Discussionmentioning
confidence: 78%
“…More details regarding the difference between EC 50mix and TU can be found the research of Tian et al (Tian et al, 2013a). In addition, the toxic ratio for most of the binary mixtures was set to 1:1 based on the Climax Hypothesis that we proposed in our previous research (Lin et al, 2005), which indicated that the joint effect was closely associated with the toxic ratio of each component and that the most obvious effect would appear at the equitoxic ratio.…”
Section: Toxicity Experimentsmentioning
confidence: 99%